Adeno-associated virus Rep proteins target DNA sequences to a unique locus in the human genome. - Surosky, R T (1997)
We have developed a system for site-specific DNA integration in human cells, mediated by the adeno-associated virus (AAV) Rep proteins. In its normal lysogenic cycle, AAV integrates at a site on human chromosome 19 termed AAVS1. We describe a rapid PCR assay for the detection of integration events at AAVS1 in whole populations of cells. Using this assay, we determined that the AAV Rep proteins, delivered in cis or trans, are required for integration at AAVS1. Only the large forms of the Rep protein, Rep78 and Rep68, promoted site-specific integration. The AAV inverted terminal repeats, present in cis, were not essential for integration at AAVS1, but in cells containing Rep, they increased the efficiency of integration. In the presence of the Rep proteins, the integration of a plasmid containing AAV inverted terminal repeats occurred at high frequency, such that clones containing the plasmid could be isolated without selection. In two of the five clones analyzed by fluorescence in situ hybridization, the plasmid DNA was integrated at AAVS1. In most of the clones, at least one copy of the entire plasmid was integrated in a tandem array. Detailed analysis of the integrated plasmid structure in one clone suggested a complex mechanism producing rearrangements of the flanking genomic DNA, similar to those observed with wild-type AAV.